Relação entre a presença de fontes de radiação não ionizante e a leucemia infantil - Cyntia Maria Moreira (2024)
Leukemia is the most common type of cancer in childhood. Among the types of childhood leukemia, acute myeloid and acute lymphoblastic leukemia prevail. This pathology is considered the most common cancer in children aged 0 to 14 years, and represents approximately one third of pediatric cancers. Electromagnetic radiation is present in the daily lives of the population and is not perceived. They are emitted by equipment such as radio antennas, telephone antennas, computers, cell phones, among others. The accelerated growth of the telecommunications industry has led to an increase in health-related problems, such as headaches, sleep disorders, infertility in men and, most worryingly, the risk of developing cancer. The general objective of this study was to analyze exposure to non-ionizing radiation sources and the development of diseases. The results of this research are presented in the form of four articles. The first is an integrative review of the literature on the relationship between non-ionizing radiation sources and cases of childhood leukemia, with the aim of analyzing the scientific evidence regarding the association between the presence of extremely low frequency electromagnetic fields and the occurrence of childhood leukemia. The second is a bibliometric review on the relationship between electromagnetic pollution and the development of diseases. These two reviews showed that there is a need for further studies to guide conclusions and decision-making about the risks or otherwise of childhood exposure to ELF-MF. The third article, a cross-sectional study with data from the Hospital Admission Authorization for childhood leukemia in Campo Grande – MS from 2010 and 2020, which showed the information can support evidence for decision-making and implementation of public health policies, when it comes to the diagnosis and treatment of childhood leukemia. And finally, an article that presents the mapping of the surroundings (400m) of homes of children diagnosed with childhood leukemia, in Campo Grande – MS, which demonstrated the existence of analysis with the frequency of cases and environmental variables within 400 meters of the homes, such as cell phone towers, gas stations, car washes, mechanic shops. The majority of residences are located in residential neighborhoods and on paved streets. These findings can support decisions regarding decision-making and implementation of policies related to public health when it comes to risk factors related to the prevention of childhood leukemia.